Fluorescent nitric oxide donor for the detection and killing of Pseudomonas aeruginosa. Issue 12 (11th February 2019) - Hibbard, Hailey A. J.; Reynolds, Melissa M.
Abstract : This paper reports a novel fluorescent nitric oxide donor for the simultaneous detection and killing of Pseudomonas aeruginosa . Abstract : The epidemic of multidrug-resistant bacteria calls for the improvement of both detection methods for bacterial infections and methods of treatment. Nitric oxide is a known potent antibacterial agent, but due to its gaseous and highly reactive nature, it is difficult to incorporate into a stable antibacterial compound. In this paper, we synthesize a nitric oxide donor attached to a fluorescent compound, creating a material that can both detect and kill the deadly multi-drug resistant bacteria strain Pseudomonas aeruginosa . Detection occurs through a bacterial enzyme-activated color change, showing a clear and obvious change from blue to yellow under UV light. The synthesized compound spontaneously releases 853 μmol of nitric oxide/g from a 10 mM initial concentration. Antibacterial efficacy studies after exposing Pseudomonas aeruginosa to a 10 mM dose of the synthesized compound show a 55–75% reduction in bacteria after 24 hours. This work is the first instance of a small molecule dual-function material that can both detect and kill bacteria.